2019
DOI: 10.1111/apv.12223
|View full text |Cite
|
Sign up to set email alerts
|

Commuting distances to local non‐farm workplaces and out‐migration: The case of Northeast Thailand

Abstract: The relationship between commuting distances and where people work has been studied for urban contexts in both developed countries and developing countries. However, few studies have examined the situation in rural areas, and none look at commuting distances to non-farm workplaces in rural areas of developing countries. This paper investigates how commuting distance, and thus accessibility, to local non-farm work influences non-farm employment and out-migration from rural villages in Northeast Thailand. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For adults who work in the formal labor sector, the workplace should be regarded as a venue for health-promoting exercise [ 27 ], e.g., by walking around the building, using stairs, and other light-to-medium PA in the office setting. Apart from recreational PA, collective active minutes could also be added from transport-related PA as part of the daily commute from home to workplace [ 28 , 29 ]. Among adults employed in the agricultural or informal labor sectors, however, farming-related activity obviously dominates the overall pattern for PA.…”
Section: Discussionmentioning
confidence: 99%
“…For adults who work in the formal labor sector, the workplace should be regarded as a venue for health-promoting exercise [ 27 ], e.g., by walking around the building, using stairs, and other light-to-medium PA in the office setting. Apart from recreational PA, collective active minutes could also be added from transport-related PA as part of the daily commute from home to workplace [ 28 , 29 ]. Among adults employed in the agricultural or informal labor sectors, however, farming-related activity obviously dominates the overall pattern for PA.…”
Section: Discussionmentioning
confidence: 99%
“…2 Various studies have highlighted the importance of proximity to the city for the mobility patterns of rural workers. A recent study in North East Thailand revealed that individuals are willing to travel up to 20 km from the villages in order to work in the factory clusters (Shirai et al 2019 ). In Indonesia, rural–urban commuting has been observed within 60-km periphery of industrialized cities (Douglass 2007 ).…”
Section: Introductionmentioning
confidence: 99%